The lived experiences of claiming wrongful conviction in prison - Burtt, EK (2019)
This thesis examines the lived experiences of prisoners who believe themselves to be wrongfully convicted. It is based on the written accounts of sixty-four prisoners who are currently maintaining innocence and offers a comparison to their ‘rightly’ convicted counterparts, as evidenced in the academic literature. What these accounts illustrate is that although this population do largely adjust to the prison environment, their experiences are constantly framed by notions of injustice and illegitimacy and it is these feelings that become the lens through which they navigate prison life.